Enhancing Parental Warmth and Reducing Family Stress: Effectiveness of the Family Empowerment Workshop - Şahin, Ayşe; Soylu, Dilek; Ghezelseflo, Mehdi (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: This study aimed to evaluate the effectiveness of the Family Empowerment Workshop in enhancing parental warmth and reducing family stress through a structured intervention involving both mothers and fathers. Method: The study employed a randomized controlled trial design with 30 participants divided into intervention (n=15) and control (n=15) groups. The intervention group attended an eight-session Family Empowerment Workshop, while the control group did not receive any intervention. Parental warmth and family stress were measured using the Parental Acceptance-Rejection Questionnaire (PARQ) and the Family Environment Scale (FES) at three time points: pre-intervention, post-intervention, and four-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests. Results: The intervention group showed significant improvements in parental warmth, increasing from a mean of 60.43 (SD = 8.12) at pre-intervention to 75.34 (SD = 7.55) post-intervention and 72.65 (SD = 7.89) at follow-up. Family stress in the intervention group decreased from a mean of 42.56 (SD = 6.32) at pre-intervention to 28.34 (SD = 5.87) post-intervention and 30.12 (SD = 6.45) at follow-up. Repeated measures ANOVA indicated significant effects for time and group on both parental warmth (F(2, 56) = 39.75, p < .001) and family stress (F(2, 56) = 52.88, p < .001), with significant interaction effects (p < .001). Bonferroni post-hoc tests confirmed significant differences between pre- and post-intervention, and pre-intervention and follow-up (p < .001). Conclusion: The Family Empowerment Workshop effectively enhanced parental warmth and reduced family stress, with sustained improvements observed at the four-month follow-up. These findings highlight the importance of structured parenting programs that address both emotional and stress management skills to foster positive family dynamics.